Complement factor D regulates collagen type I expression and fibroblast migration to enhance human tendon repair and healing outcomes - Chen, Junyu; Wang, Jin; Hart, David A.; Zhou, Zongke; Ackermann, Paul W.; Ahmed, Aisha S. (Frontiers in Immunology, 2023)
Dense connective tissues (DCTs) such as tendon, ligament, and cartilage are important stabilizers and force transmitters in the musculoskeletal system. The healing processes after DCT injuries are highly variable, often leading to degenerative changes and poor clinical outcome. Biomarkers in relation to repair quality for human DCTs, especially tendon are lacking. This study expands our previous findings and aimed to characterize the mechanisms by which a potential biomarker of good outcomes, complement factor D (CFD), regulates tendon healing. Quantitative mass spectrometry (QMS) profiling of tissue biopsies from the inflammatory phase of healing (n = 40 patients) identified 769 unique proteins, and microdialysates from the proliferative phase of healing (n = 28 patients) identified 1423 unique proteins in Achilles tendon rupture patients. QMS-profiling showed that CFD expression was higher during the inflammatory-and lower during the proliferative healing phase in the good outcome patients. Further bioinformatic and experimental explorations based on both inflammatory and proliferative fibroblast models demonstrated that CFD potentially improved repair by regulating cell migration and modulating collagen type I (Col1a1) expression. Moreover, it was shown that the enhanced Col1a1 expression, through increased fibroblast migration, was correlated with the validated clinical outcome. The results of the current studies characterized underlying inflammatory-and proliferative healing mechanisms by which CFD potentially improved tendon repair. These findings may lead to improved individualized treatment options, as well the development of effective therapies to promote good long-term clinical outcomes after tendon and other DCT injuries.